LA GEOMATICA PER LA VALUTAZIONE DELLA RISORSA ENERGIA DAL MARE: PROGETTAZIONE E SVILUPPO DSS -WEB GIS "WAVES ENERGY” - Pollino, Maurizio; La Porta, Luigi; Caiaffa, Emanuela (GEOmedia, 2015)
GIS methodologies and technologies are able to provide useful tools for the assessment of sea-waves energy potential, by evaluating both the exploitability of such resource, both the environmental/social impacts in open sea and/or in the coastal areas. The DSS-WebGIS application developed (called "Waves Energy") is a tool for providing and publishing different geospatial data, sharing information with a wide range of external user, in order to support specific tasks, such as forecasting, new installations planning and existing infrastructures management.